2012
DOI: 10.1017/s1368980012002844
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Omani adults’ physical inactivity and sitting time

Abstract: Objective: To inform public health approaches for chronic disease prevention, the present study identified sociodemographic, anthropometric and behavioural correlates of work, transport and leisure physical inactivity and sitting time among adults in Oman. Design: Cross-sectional study using the WHO STEPwise study methodology. Setting: Sur City, Oman. Subjects: Men and women aged 20 years and older (n 1335) in the Sur City Healthy Lifestyle Study who had complete data for demographic variables (gender, age, ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 32 publications
0
45
0
7
Order By: Relevance
“…A national survey reported that 67% of men and 59% of women met physical activity guidelines (9), while another survey, among college students, reported that 56.6% of men and 42.2% of women college students met these guidelines (10). Findings from the city of Sur in the east of Oman found that women were more active in the work domain compared with men, that men were more active in the transport and leisure domains, and that physical activity had an inverse association with the presence of metabolic syndrome (11). Here we report on the prevalence and correlates of domain-specific physical activity among Omani adults at the national level and consider the implications for the prevention of major noncommunicable diseases.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…A national survey reported that 67% of men and 59% of women met physical activity guidelines (9), while another survey, among college students, reported that 56.6% of men and 42.2% of women college students met these guidelines (10). Findings from the city of Sur in the east of Oman found that women were more active in the work domain compared with men, that men were more active in the transport and leisure domains, and that physical activity had an inverse association with the presence of metabolic syndrome (11). Here we report on the prevalence and correlates of domain-specific physical activity among Omani adults at the national level and consider the implications for the prevention of major noncommunicable diseases.…”
Section: Introductionmentioning
confidence: 84%
“…A study in Sur, Oman, found a similar association among men of all ages for the leisure domain only, but not among women (11). Similarly, young unmarried women in Saudi Arabia have been found to be less active than married women (23).…”
mentioning
confidence: 93%
“…Há evidências de que baixos níveis de escolaridade e renda estão relacionados a uma chance diminuida no engajamento em AF moderadas à vigorosas e de lazer 22 . Em relação a intensidade de AF praticada neste estudo, curiosamente ambos os grupos etários apresentaram maior prevalência em atividades de caminhada, seguida da atividade moderada, enquanto é observado na literatura que os homens, usualmente, praticam atividades vigorosas 23 . Entretanto deve-se levar em conta, que os resultados na literatura consideram amostras com idade de até 35 anos, na qual há elevada prática de AF principalmente no lazer, com atividades como futebol e musculação.…”
Section: Discussionunclassified
“…Entretanto deve-se levar em conta, que os resultados na literatura consideram amostras com idade de até 35 anos, na qual há elevada prática de AF principalmente no lazer, com atividades como futebol e musculação. Ao passar dos anos o interesse por tais atividades se modifica, preferindo-se atividades mais leves, como a caminhada, sendo a mais comum em populações com idade superior a 40 anos [23][24][25] . Nesta perspectiva, considerando a intensidade da AF, neste estudo identificou-se influência da percepção de saúde.…”
Section: Discussionunclassified
“…Global Physical Activity Questionnaire (GPAQ), International Physical Activity Questionnaire (IPAQ-Short) and locally developed questionnaires), the population estimate for adults meeting WHO PA recommendations in Arab countries is around 40% for men and 27% for women [10]. A regional study in Sur (north-east coast of Oman), using GPAQ, showed the highest levels of physical inactivity were in leisure time (55%) and the median sitting time was about two hours/day [11]. …”
Section: Introductionmentioning
confidence: 99%